The great American bar scene [compact disc] - Bryan, Zach, 1996- (Warner Records, 2024)
Zach Bryan has become one of the fastest rising stars in country music today, with a chart topping single among his many accolades. Following a digital release in July, his fifth album is available to order on CD.